Diversity in Unity: An Analysis of Multicultural and Multi-Religious in a Biblical Gender Perspective - Nuniek Ernaningrum (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Modernization creates diversity in both culture and religion. This fact requires the ability to respond to it to maintain integrity or unity. The problem is more complicated when it comes to globalization, which results in the rejection of collective self-expression and fosters liberal individualism. This situation often triggers violence at the personal level (domestic violence) and the general level (religion-based violence). The consequence is that maintaining unity both at the private (domestic) and public levels is an urgency to find solutions. This study aims to find a philosophical unity formula and its tools. For this reason, this research will be divided into several topics: diversity from a sociological perspective, diversity in the Christian perspective, the concept of unity in the Christian perspective, and the set of the conception of unity in the Christian perspective. This study aims to obtain a philosophical formula for unity from a Christian perspective. This research is evaluative research, so the research method is carried out using type A Critical Mode of Inquiry through literature study. The findings of this study are that the philosophical conception of gender according to the Bible can be the answer to the creation of unity and the church is one of the stakeholders in implementing change.